Comparison of Electrofishing Techniques and Effort Allocation across Diel Time Periods, Seasons, Sites, and Habitat in the Ohio Coastal Waters of Western Lake Erie. (2nd January 2016) - Ross, J. E.; Mayer, C. M.; Tyson, J. T.; Weimer, E. J.
Abstract: Coastal (<3-m depth) and nearshore (3–15-m depth) zones of large freshwater lakes are generally rich in complex habitats that are important for fisheries, but they are often highly degraded and understudied. We identified spatial and temporal sampling efficiencies for monitoring coastal fish communities in a large freshwater lake by use of electrofishing. During 2011 and 2012, we sampled 21 coastal sites in Lake Erie's western basin via daytime and nighttime electrofishing with multiple replicates throughout the summer sampling season. Nighttime electrofishing captured more species and more individuals with less effort than daytime electrofishing; nighttime electrofishing conducted early in the season (i.e., late spring and early summer) was more efficient than that conducted late in the season (i.e., late summer and early fall). A sampling design based on 500 m of shoreline per site required fewer sites and person-hours to attain 65% and 75% of total species richness (6 and 11 sites, respectively) than a design that used 100 m/site. A 300-m/site design was more efficient at targeting 90% of total species richness. Targeting of wetland habitat increased the number of species captured but missed species that were only found at other habitat types. A sampling design that targeted 11 sites (75% of species richness) sufficiently described fish community metrics (e.g., number of tolerant species) since the design captured nearly all fish species that were relevant to each metric. This study provides the foundation for a coastal monitoring program in western Lake Erie and serves as a starting point for program development in other large freshwater lakes. Received January 16, 2015; accepted October 8, 2015